PELAKSANAAN PROGRAM KARTINIAN DALAM MENINGKATKAN ANTUSIASME BELAJAR - Roni Firmansyah; Velisha Putri Andella; Maharani Tia Putri; Dhea Mareta; Alia Rohali; Elda Yuniar; Rio Chandra Winata; Fathurrahman Fahlevy; Syska Purnama Sari (STKIP Subang, 2026)
This study aims to evaluate the implementation of the Kartinian Program in stimulating students' learning enthusiasm while mapping out the supporting elements of its success. A qualitative approach utilizing a case study design was employed. Data collection involved direct observation, in-depth interviews, and document analysis with the school principal, teachers, and students as active participants. To understand the phenomenon comprehensively, the data analysis progressed through data reduction, data display, and conclusion drawing. The results demonstrate that the Kartinian Program effectively boosts students' learning enthusiasm through creative, participatory, and experiential learning activities. The core themes identified include enhanced learning motivation, active engagement in the learning process, and a broader understanding of emancipation values, cultural heritage, and character building. These findings confirm that national holiday celebrations can serve as an alternative educational strategy to create a more engaging and meaningful academic atmosphere. This study contributes significantly to fostering learning innovations in schools and offers practical insights for replicating similar programs in other educational settings.